GENDER DISCRIMINATION ON THE MAIN CHARACTER FIRDAUS IN THE NOVEL “WOMAN AT POINT ZERO” BY NAWAL EL SAADAWI - Rismawati, Bau; Sunra, La (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
Women have long suffered because of gender discrimination. In patriarchal societies, discrimination is more fatal due to its homogeneous beliefs and values. This discrimination against women often leads to mental problems for some individuals. Literature serves as a fitting platform to voice social issues, including gender-based discrimination. This study aims to analyze the gender discrimination reflected in the novel